Comparative Microbiomics of Tephritid Frugivorous Pests (Diptera: Tephritidae) From the Field: A Tale of High Variability Across and Within Species - De Cock, Maarten; Virgilio, Massimiliano; Vandamme, Peter; Bourtzis, Kostas; De Meyer, Marc; Willems, Anne (Frontiers in Microbiology, 2020)
The family Tephritidae includes some of the most notorious insect pests of agricultural and horticultural crops in tropical and sub-tropical regions. Despite the interest in the study of their gut microbiome, our present knowledge is largely based on the analysis of laboratory strains. In this study, we present a first comparative analysis of the gut microbiome profiles of field populations of ten African and Mediterranean tephritid pests. For each species, third instar larvae were sampled from different locations and host fruits and compared using 16S rRNA amplicon sequencing and a multi-factorial sampling design. We observed considerable variation in gut microbiome diversity and composition both between and within fruit fly species. A “core” microbiome, shared across all targeted species, could only be identified at most at family level (Enterobacteriace). At genus level only a few bacterial genera (Klebsiella, Enterobacter and Bacillus) were present in most, but not all, samples, with high variability in their relative abundance. Higher relative abundances were found for seven bacterial genera in five of the fruit fly species considered. These were Erwinia in Bactrocera oleae, Lactococcus in B. zonata, Providencia in Ceratitis flexuosa, Klebsiella and Rahnella in C. podocarpi and Acetobacter and Serratia in C. rosa. With the possible exception of C. capitata and B. dorsalis (the two most polyphagous species considered) we could not detect obvious relationships between fruit fly dietary breadth and microbiome diversity or abundance patterns. Similarly, our results did not suggest straightforward differences between the microbiome profiles of species belonging to Ceratitis and the closely related Bactrocera/Zeugodacus. These results provide a first comparative analysis of the gut microbiomes of field populations of multiple economically relevant tephritids and provide base line information for future studies that will further investigate the possible functional role of the observed associations.